STRATEGI INDONESIA DALAM MENINGKATKAN EKSPOR CRUDE PALM OIL (CPO) KE PAKISTAN TAHUN 2007-2013 - Ilham Satriadi; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study analyzes the strategies used to increase to export of Indonesiancrude palm oil (CPO) to Pakistan. Indonesia signed a preferential trade agreement toPakistan in 2012. The main reason that prompted Indonesia to sign a tradepreference is to optimize the export of CPO and for better cooperation.This study would also explain the trip Indonesia began negotiationsFramework for Comprehensive Economic Partnership (FACEP) by Indonesia andPakistan signed in 2005, both from the development and scope negotiations. Inaddition, this study also discusses the barriers, opportunities and challenges of whatis in the can from the cooperation between Indonesia and Pakistan.Keywords: Export CPO, Strategy, Preferential Trade Agreement.